2003
DOI: 10.1034/j.1601-5223.2003.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Segmental allopolyploidy and paleopolyploidy in species of Leucaena Benth: evidence from meiotic behaviour analysis

Abstract: In this paper we report meiotic behaviour in 28 accessions of the tetraploid (2n = 4x = 104 or 112) Leucaena confertiflora, L. diversifolia, L. involucrata, L. leucocephala, L. x spontanea and the diploid (2n = 2x = 52 or 56) L. shannonii and L. macrophylla. We compare and discuss our data with that on literature about polyploidy in the genus. Despite the general predominance of bivalent formation, quadrivalents and other associations were found in all the taxa analysed. In the diploid species. multiple associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…These authors observed that 26% of the species analyzed were polyploids and that at least 3 of them exhibited intraspecific polyploidy. A similar evolutionary pattern of polyploidy was also observed in other South America species of Mimosa (Seijo and Fernández, 2001) and Leucaena (Boff and Schifino-Wittmann, 2003). A total of 13 species of the genus Inga from northeastern Brazil were analyzed, and 4 were found to be polyploids (2 of them showing intraspecific polyploidy; Mata, 2009, unpublished data).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These authors observed that 26% of the species analyzed were polyploids and that at least 3 of them exhibited intraspecific polyploidy. A similar evolutionary pattern of polyploidy was also observed in other South America species of Mimosa (Seijo and Fernández, 2001) and Leucaena (Boff and Schifino-Wittmann, 2003). A total of 13 species of the genus Inga from northeastern Brazil were analyzed, and 4 were found to be polyploids (2 of them showing intraspecific polyploidy; Mata, 2009, unpublished data).…”
Section: Discussionmentioning
confidence: 86%
“…In Leucaena, for example, there are paleopolyploid species with 2n = 52 and 58, suggesting that there may have been 2 basic numbers-1 originating through disploidy from an ancestral stock with x 2 = 26 (Boff and Schifino-Wittmann, 2003). Genera, such as Desmanthus, Entada, and Prosopis (Table 2), have the basic number x = 14, which apparently resulted from ascending disploidy from a principal lineage with x = 13.…”
Section: Discussionmentioning
confidence: 99%
“…coccineus, 2n=22 (Castagnaro et al 1990); c. células somáticas en metafase de Astragalus pehuenches, 2n=22 (Dopchiz et al 1995); d. metafase de Senna chloroclada 2n=28; e. cromosomas somáticos de Vicia pampicola, 2n=14 (Naranjo et al 1998); f. metafase de Bauhinia uruguayensis, 2n=26; g. hibridación in situ de Galactia fiebrigiana, 2n=20 (Sede et al 2006); h. hibridación in situ de Collaea stenophylla, 2n=20, usando como sonda la región rDNA pTa71 (Sede et al 2006). La barra en las figuras a-f representa 10 µm y g-h 5 µm a b c d e f g h sugieren que la hibridación interespecífica y poliploidía han sido relevantes en su evolución (n=13, 26, 52,104/14, 28, 56, 112); como antecedente se indica que Leucaena presenta especies de origen híbrido homoploide y poliploide, y polimorfismo numérico para cromosomas accesorios (cromosomas B), lo cual complica los análisis convencionales de relaciones especificas tanto a nivel taxonómico como evolutivo (Hughes et al 2002;Boff & Schifino Wittman 2003). Calliandra es atípico en la tribu Ingeae, por ser el único representante genérico con 2n=16 cromosomas.…”
Section: Análisis Filogenético De La Variación Cromosómicaunclassified
“…Os dados de comportamento meiótico sugerem uma origem alopoliplóide segmentar sensu STEBBINS (1971), apesar de a autopoliploidia não poder ser descartada. Até 7% (BOFF & SCHIFINO-WITTMANN, 2003) ou mesmo 12% de gametas não reduzidos podem ocorrer em L. trichandra. A identificação de um poliplóide natural em L. trichandra sugere que a autopoliploidia pode ocorrer em Leucaena.…”
Section: Comportamento Meióticounclassified